Energy Bands of Acceptor-Type Graphite Intercalation Compounds - Zaleski, Henryk (My University, 1985)
Reaction of graphite with liquid antimony pentachloride produced stage 1 and 2 intercalation compounds. A stage-1 SbF₆-compound was prepared by reaction of graphite with nitryl hexafluoroantimonate in solution and by reaction with the solid salt. Reaction of solid nitryl tetrafluoroborate with graphite produced a stage-2 compound.
The de Haas-van Alphen spectrum of the stage-1 SbCl₅ compound had a dominant oscillation of 1212 T. The oscillation was identified with the basic graphitic band. The dHvA spectrum of the stage-2 SbCl₅ compound depended on the cooling rate between room temperature and 77 K. The spectra of slowly-cooled samples had two fundamental oscillations of frequencies of 422 and 1190 T which were identified with the basic graphitic bands. Beat patterns of the fundamental frequencies were explained by doubling of the c-axis lattice constant. From the beat frequencies values of the interaction between states localized on graphene layers separated by an intercalate layer were estimated to be 0.6 meV and 0.7 meV. From these values the anisotropy of the conductivity was calculated to be 9x10⁴.
The dHvA spectra of stage-1 SbF₆⁻ compound depended on the method of preparation. With samples prepared by reaction of solid NO₂SbF₆, a dominant frequency of 1627 T was observed. Two fundamental oscillations of frequencies of 523 and 1877 T were observed in the spectrum of stage-2 BF₄⁻ compound and were identified with the basic graphitic bands.
The predictions of the rigid band model of Holzwarth (1980) were in agreement with measured dHvA frequencies and cyclotron masses with the Fermi energy adjusted to the charge transfer in each compound. The fitted values are -1.12 eV for stage-1 SbCl₅ compound, -0.88 eV for stage-2 SbCl₅, -1.28 eV for stage-1, SbF₆⁻ and -0.96 eV for stage-2 BF₄⁻ compound. The simpler model of Blinowski et al. (1980) was found less accurate.
Keywords: Physics; Physics